Potential physical distance in the open urban grey space of city counties in Poland and COVID-19 cases and deaths throughout the pandemic - Roman Suligowski; Tadeusz Ciupa (Archives of Public Health)
Abstract Background This paper reports the structure of grey space and the number of cases and deaths throughout the COVID-19 pandemic (from March 2020 to June 2023) in 66 city counties in Poland. Methods Three main components of urban grey space (built-up areas, transport areas, and industrial areas) and the potential physical distance between residents in the open grey space – was determined. The total number of COVID-19 cases and deaths covered the entire period of the pandemic (totalling 1,214 days) was identified. The incidence and mortality density rates and the case fatality ratio were calculated. Simple and multiple linear regression models were developed to predict the quantitative characteristics of COVID-19 independent of city size. Results Within the open spaces of cities, the average distance between residents was 17.7 m and was several times greater than that in closed spaces (1.5–2.0 m), which significantly reduced the risk of COVID-19 infection. Strong relationships were observed between the potential physical distance in the grey space structure and the total number of COVID-19 cases and deaths. The coefficient of determination (R2) for these relationships in the eight city groups by population was 0.90 for cases and 0.88 for deaths (significance level p = 0.001). Conclusion The study contributes to understanding how potential physical distance based on population density in grey space, might have influenced the course of COVID-19 during the pandemic. These findings can be applied to planning antiviral protection and to implementing future multilevel restrictions aimed at reducing the reproduction of SARS-CoV-2 in cities of various sizes.